Health facilities in the homes of pupils in San Fernando, Pampanga and their implications for health education - Eusebio, Virginia (Sanchez) (s.n.], 1974)
This study determined the health facilities provided in the homes of pupils in San Fernando, Pampanga and their implications in health education using the normative survey method. Findings revealed that though these facilities existed in the homes of the pupils, the quantity and quality of these health facilities depended on factors like individual, family and regional economics, ways of working and living of the people, education, socio-economic status, value system, acculturation, means of transportation and communication, availability of materials and funds, means of livelihood, subculture, better resources and geographical location.